2010
DOI: 10.3390/molecules15020689
|View full text |Cite
|
Sign up to set email alerts
|

Chemical Analysis and Biological Activity of the Essential Oils of Two Endemic Soqotri Commiphora Species

Abstract: The barks of two endemic Commiphora species namely, Commiphora ornifolia (Balf.f.) Gillett and Commiphora parvifolia Engl., were collected from Soqotra Island in Yemen and their essential oils were obtained by hydrodistillation. The chemical composition of both oils was investigated by GC and GC-MS. Moreover, the essential oils were evaluated for their antimicrobial activity against two Gram-positive bacteria, two Gram-negative bacteria and one yeast species by using a broth micro-dilution assay for minimum in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
22
0
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 36 publications
(25 citation statements)
references
References 20 publications
2
22
0
1
Order By: Relevance
“…The major constituents of the essential oil from Commiphora species are terpenoids, which vary from species to species . Several studies on other Commiphora species revealed the presence of mostly monoterpenoids and sesquiterpenoids in their essential oils . For instance, the GC–MS analysis of C. myrrha essential oil revealed the presence of a relative abundance of 58.9% monoterpenes and 23.3% sesquiterpenes .…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The major constituents of the essential oil from Commiphora species are terpenoids, which vary from species to species . Several studies on other Commiphora species revealed the presence of mostly monoterpenoids and sesquiterpenoids in their essential oils . For instance, the GC–MS analysis of C. myrrha essential oil revealed the presence of a relative abundance of 58.9% monoterpenes and 23.3% sesquiterpenes .…”
Section: Resultsmentioning
confidence: 99%
“…It has been shown that Commiphora species display a wide range of biological activities, including antimicrobial, anti‐inflammatory, antioxidant, and anticancer activities . No studies have been conducted on the biological activity of C. wildii essential oil, however.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Essential oils of the plant Lavandula dentata of eastern Maroco, that contains about 3% myrtenol was found to have antibacterial activity against E. coli, Salmonella sp., Neisseria meningitidis, S. aureus, Streptococcus pneumonia, Listeria monocytogenes (Imelouane et al, 2009). Essential oils of Commiphora ornifolia bark collected from Soqotra Island in Yemen, that contains about 0.7% myrtenol was also found to inhibit growth of bacteria S. aureus, B. subtilis, E. coli and Pseudomonas aeruginosa (Mothana et al, 2010).…”
Section: Discussionmentioning
confidence: 99%
“…Several studies demonstrated that, the antibacterial activity of many essential oils and spices could be ascribed to the presence of phenolic components or substances other than phenolic compounds (82) , presence of linalool and ß-pinene (83,48) , oxygenated monoterpenes such as camphor, borneol, linalool and α-terpineol (85)(86)(87) . Moreover, the compounds present in the greatest proportions are not necessarily responsible for the total activity; the involvement of less abundant constituents should also be considered (88) , the presence of synergy between the major components and other constituents of the oils leading to various degrees of antimicrobial activity.…”
Section: Antibacterial Activitymentioning
confidence: 99%